2022
DOI: 10.1371/journal.pone.0263220
|View full text |Cite
|
Sign up to set email alerts
|

Integrating quantitative and qualitative approaches to assess wintertime illness-related absenteeism and its direct and indirect costs among the private sector in Ulaanbaatar

Abstract: Causes for employee absenteeism vary. The commonest cause of work absenteeism is “illness-related.” Mongolia’s capital city, Ulaanbaatar, experiences high employee absenteeism during the winter than during other seasons due to the combination of extreme cold and extreme air pollution. We identified direct and indirect costs of absenteeism attributed to air pollution among private-sector employees in Ulaanbaatar. Using a purposive sampling design, we obtained questionnaire data for 1,330 employees working for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…A previous study including employees who worked for the private sector in Ulaanbaatar reported that respiratory disease was the major cause of SA, especially during winter, but that most SA was uncertified. 9 Factors associated with taking a long-term absence among HCWs who had SA were the age group ≥40 years old, 10-19 years in employment compared with 9 years or less, working at the secondary and tertiary levels compared with the primary level, and having night shifts. Older age and longer experience were associated with having a longterm SA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study including employees who worked for the private sector in Ulaanbaatar reported that respiratory disease was the major cause of SA, especially during winter, but that most SA was uncertified. 9 Factors associated with taking a long-term absence among HCWs who had SA were the age group ≥40 years old, 10-19 years in employment compared with 9 years or less, working at the secondary and tertiary levels compared with the primary level, and having night shifts. Older age and longer experience were associated with having a longterm SA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study including employees who worked for the private sector in Ulaanbaatar reported that respiratory disease was the major cause of SA, especially during winter, but that most SA was uncertified. 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations